Exploring the Potential Role of Terrestrially Derived Humic Substances in the Marine Biogeochemistry of Iron - Muller, François L. L. (Frontiers in Earth Science, 2018)
There is a widely recognized link between iron bioavailability and phytoplankton growth in large tracts of the World Ocean. Iron bioavailability is thus pivotal to the removal of atmospheric carbon via the ocean’s ‘biological pump.’ To evaluate future scenarios of global climate change, we must therefore understand better how the bioavailability of iron in seawater is linked to processes controlling its supply, chemical speciation and removal from the water column. Much of the research on iron inputs to the open ocean has focused on atmospheric, benthic (shelf sediments) and hydrothermal (mid-ocean) sources of iron. The conventional wisdom has been that riverine iron sources are negligible because many of the major world rivers exhibit extensive removal of dissolved iron by flocculation processes during estuarine mixing. However, recent studies have revealed that a fraction of iron associated with peatland-derived humic and fulvic acids may survive aggregation processes in the freshwater-seawater mixing zone, and thus be exported offshore. This review is a synthesis of available data and information for and against the hypothesis that land-derived humic substances exert a significant control on the marine biogeochemical cycle of iron. From the outset, it is shown that this hypothesis can neither be verified nor disproved at present, in part due to analytical difficulties in characterizing the all-important marine colloidal phase. Evidence is then presented on the likely chemical nature and structure of iron-binding humic ligands along with implications for the lateral transport of iron in surface waters and its participation in carbon stabilization in marine sediments. This is followed by a discussion of photochemically and microbially mediated processes acting on terrestrial humic substances and a discussion of how terrestrial humic substances may influence the biological availability of iron. The review finishes with a presentation of measurement technologies and approaches that could be used to assess (i) how iron-binding ligands in seawater relate to land-derived humic substances and (ii) how terrestrial humics may influence the global carbon cycle indirectly by influencing the processes that control the supply and maintain the pool of ‘dissolved’ iron in the ocean.